Priceless [videorecording (DVD)] - Smallbone, Ben; Smallbone, Joel; Smallbone, Joel; Santos, Bianca A., 1990-; Midthunder, Amber (Universal Pictures Home Entertainment, 2017)
A widower who loses custody of his daughter finds himself unable to hold down a job. He agrees to drive a truck across the country, no questions asked. When he discovers what he is delivering, he is faced with a life-changing choice.